G161(P) Creating a mental health workshop for secondary school children. (7th April 2014) - Webb, NL; Mair, J; Cook, E
Abstract : Background: In the UK 1 in 10 children aged 5–16 has a mental health disorder, and 80, 000 young children and adolescents are living with severe depression. Despite published evidence highlighting the reduction in psychiatric morbidity when mental health disorders are identified early, interventions designed to identify individuals affected by the childhood epidemic of mental health disorders in the UK remain limited. Objectives: Education provides a powerful tool in combating mental illness. We set out to create, deliver and assess the educational impact of a mental health workshop for secondary school children. Methods: A two-hour workshop was delivered to two classes in a state secondary school in Bristol. Targeted students' awareness of mental illness, the stigma surrounding issues of mental health and the promotion of appropriate help seeking behaviours were assessed with a questionnaire. This questionnaire was delivered before and after the workshop to assess the impact of the workshop on students' knowledge in these areas. Results: Following the workshop there was improvement in Students' knowledge (49% total score time point 1, 99% total score time point 2, Figure 1 ) and attitudes towards issues of mental health. As well as greater factual knowledge assessed by questionnaire, the students displayed improved attitudes towards mental health during the concluding discussions of the workshop. Conclusions: A short workshop can increase awareness and knowledge of mental health disorders in adolescents. Previous studies have shown that young people are more likely to seek help if they recognise and have knowledge about their mental health problem. Future studies need to assess the long-term effectiveness of educational workshops. Further development of short interventions in schools could prove enormously beneficial at a time when the cost difference between prevention and cure is more important than ever.